Aplikasi Pembelajaran Kimia Untuk Sma Berbasis Multimedia Menerapkan Metode Computer Assisted Instruction (Studi Kasus: Sma Negeri 1 Perbaungan) - Simanjuntak, Halimatun Sakdiah (STMIK Budi Darma, 2018)
The Computer Assisted Instruction (CAI) method is one method of learning that uses computer equipment as a tool to help together with a knowledge base (basic knowledge). The method of computer-assisted instruction (CAI) is very popular with several teaching institutions in high school in chemistry subjects. One of the material is the periodic system of elements. Where in chemistry learning there are still many in high school in North Sumatra especially in Perbaungan N1 High School whose material includes abstract, memorized and countable things so that it is difficult for students to understand when studied only in the form of two-dimensional images. To overcome these problems, it is necessary to change the learning process from delivering material that only uses books and computers that are very helpful in the application of computer-assisted instruction (CAI) methods, it is also based on research that computers can train concentration in children and can overcome boredom and boredom. In addition computers, today are no longer a rare item and are goods that are almost mandatory for all people and institutions so that the conversion of the media is increasingly possible to be realized.